Measurement of the DC current based on magnetic fluids with an orthogonal magnetic field - Jian-Ying Zhang; Chuan-Qiang Che; Qiong Wang; Da-Peng Xu; Shuai Yuan (Measurement + Control, 2020)
Measurement of DC current is critically important in a wide range of applications, such as in photovoltaic power generation and DC power transmission. In this paper, the DC current measuring method based on magnetic fluids with orthogonal magnetic fields is studied. Firstly, the induced voltage of measurement coil, which contains a series of harmonics and the amplitude of its fundamental component is 2.5 times larger than that of other components, is derived and analyzed. Then, influence factors of the induced voltage are systematically studied. As a result, with a DC component injection into the exciting current, the frequency of the induced voltage becomes a half of that without a DC component, and when the DC component reaches to or exceeds the amplitude of the AC component, the induced voltage nearly has no distortion. Finally, the input-output characteristic of the measurement method is examined, and the accuracy, measuring range, and sensitivity are discussed, indicating that the linearity of the foundamental component root mean square (RMS) value curve is better than the one of the voltage amplitude curve under the same DC current range, and the sensitivities of induced voltage amplitude and the fundamental component RMS value are 5.948 and 3.717 mΩ, respectively.